ANALISIS POTENSI RISIKO POSTUR KERJA PEMBATIK PADA UMKM MURIA BATIK KUDUS - Mia Ajeng Alifiana; Akh. Sokhibi; Dina Lusianti (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
One of the non-object cultural heritages owned by the Indonesian people is batik. Batik is a typical Indonesian cloth spread throughout the archipelago. The process of making batik is mostly still traditional, starting from the process of making patterns on the mori cloth to the process of preparing the cloth, giving patterns, nglowong / canting, isen-isen, nembok, first coloring / medel, ngerok, mbironi stage, second coloring / greeting , nglorod and washing batik. In this batik-making process, the batik workers work continuously with a detailed type of work and the work posture of the batik is on a chair that is not designed with the dimensions of the body of the batik maker. This is if the work posture is not improved, it creates a potential risk of muscle fatigue or musculoskeletal disorder. The method used in this research is quantative. The data taken in this study is the data on the size of the batik work posture when sitting on a chair. Then the data is analyzed using the REBA (Rapid Entire Body Assessment) method using ergofellow software to determine the risk of work posture. The result of this research is the potential risk of the work position of Muria Batik Kudus UMKM batik makers with the REBA method resulting in a score of 9 (Nine), which means that they have risk criteria at a high level. The potential risk that is at a high level should immediately improve the work posture of the batik which is supported by changes in work facilities. Batik makers who have the potential for high levels of risk can result in muscle fatigue in certain parts of the body and decreased levels of productivity.